Pengukuran Kepercayaan dan Minat Dalam Menggunakan E-money - Nadia Ika Purnama; Muhammad Arif; Muhammad Andi Prayagi (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2022)
Purpose - This study aims to determine the factors that influence trust and interest in using e-money in Medan City.Methodology - The population in this study is the people of Medan City who already know about e-money as a tool for making transactions. The sampling method used in this study was purposive sampling. The sample criteria in this study are Indonesian people who use e-money products issued by 26 companies that already have official permits from Bank Indonesia. While the sample size in this study was 200 people. The data source in this research is the primary data source. Data collection techniques used. The data analysis method used is the Structural Equation Model from the LISREL 8.80 statistical software package.Findings - The results showed that Perceived Benefit had a positive effect on Trust significantly. Perceived benefits have a positive effect on interest significantly. Perceived risk has a negative effect on trust significantly. Perceived risk has a negative effect on interest significantly. Trust has a positive effect on interest significantly. Trust can positively mediate the effect of Perceived Benefits on Interest and trust can mediate the effect of Perceived Risk on Interest.Originality/Novelty - The research model uses four (4) variables and applies the concept of mediation, where each relationship in the research model is analyzed with SEM-Lisrel.Implications - This study has shown that trust has a mediating effect on the effect of perceived benefits and perceived risks on interest. Starting from the results of this study, the recommendation for further research is to try to analyze or use the trust variable as an independent variable, not as a mediating variable.